Characterisation of ZnO thin films doped and co-doped grown by pneumatic spray pyrolysis. (1st January 2013) - Chouikh, F.; Beggah, Y.; Mati, H.; Bouznit, Y.; Birem, M.; Ariche, N.; Aida, M.S.
From all the transparent conducting oxides (TCOs) studied in recent years, zinc oxide has emerged as one of the most promising materials. In the present work and in the order to obtain the high TCO materials, ZnO films were deposited by pneumatic spray pyrolysis technique on glass substrates. Our interest is on the investigation of the doping kinds influence on the structural and optical properties of ZnO thin films. One has used two dopants i.e., Bi and Sn. All the films were found to be polycrystalline and show a (0 0 2) preferential growth, the preferred orientation does not depend on the nature of dopant. The optical characterisation of deposited films was carried out using UV-Vis spectrometry. The analysis of the transmittance spectra allows us to deduce the films thicknesses and optical band gaps. Hence, the values of the gap were found to be between 3.24 to 3.32 eV.